Pelatihan Pengelolaan Lahan Berkelanjutan Berbasis Pengalaman dan Penggunaan Aplikasi Sipindo - Desi Nadalia; Baba Barus; Budi Nugroho; Arief Hartono; Darda Effendi; Hari Agung; Reza Hanjaya; Sri Malahayati Yusuf; Suria Darma Tarigan (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Horticultural plant products are daily-consumed need. These plants have developed with various cultivation techniques, i.e the selection of fertilization type. In additional to anorganic synthetic fertilizer, farmers also use the organic fertilizers in their farm. In the digital 4.0 era, information about agricultural cultivation are available in various media, such as via cell phones. Sipindo Apps is one of the specific location-based for agricultural application. The cultivation information of certain crops in Sipindo application can be used to implement sustainable land management. The aim of this activity is to disseminate the information about sustainable land management and the use of the Sipindo application to the community, students, farmers, and practitioners. This activity was delivered through structured training and field practices. The results obtained from this activity are increase participants’ ability related to making organic fertilizers and understanding sustainable land management, and participants are able to understand about the Sipindo and the use of fertilizer information contained in the application. In detail, 69% participants were able to well-understand the training material. Based on the benefit aspect, 70% of participants stated that the training was very useful.